2021
DOI: 10.1002/adma.202101845
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Microdomains of Oxides in High‐Entropy Alloy Electrodes toward Efficient Oxygen Evolution

Abstract: One important goal of the current electrocatalysis is to develop integrated electrodes from the atomic level design to multilevel structural engineering in simple ways and low prices. Here, a series of oxygen micro‐alloyed high‐entropy alloys (O‐HEAs) is developed via a metallurgy approach. A (CrFeCoNi)97O3 bulk O‐HEA shows exceptional electrocatalytic performance for the oxygen evolution reaction (OER), reaching an overpotential as low as 196 mV and a Tafel slope of 29 mV dec−1, and with stability longer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 60 publications
(17 reference statements)
0
57
0
Order By: Relevance
“…The long-term stability of CoMoP was further analyzed by CV and chronopotentiometry measurements [ 57 , 58 ]. Figure 4 e shows how the LSV curve of CoMoP after 3000 CV cycles closely resembles that of the first cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term stability of CoMoP was further analyzed by CV and chronopotentiometry measurements [ 57 , 58 ]. Figure 4 e shows how the LSV curve of CoMoP after 3000 CV cycles closely resembles that of the first cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, heterogeneous catalysts construction and morphological control are also paramount to further adjusting their catalytic performances. 108,109,[117][118][119][120] For example, Shi et al 107 reported the non-NM HEA as a substrate to disperse, stabilize, and tune NM Pt (active sites) toward significantly improved activity, stability, and low cost. In their design, the surface Pt nanoclusters are anchored on the non-noble HEA core, which ensures high dispersity, stability, and tunability of the surface active sites through high-entropy stabilization and core-shell interactions (Figure 5C).…”
Section: Heterogenous Construction and Morphology Controlmentioning
confidence: 99%
“…The DFT calculations show that Ni/Co can reduce the barrier potential of rate-determining step (O*→OOH*), and Al sites can promote the electrical conductivity ( Feng et al, 2020 ). Yu et al introduce Cr into representative NiCoFe system to synthesize (CrFeCoNi) 97 O 3 , and Cr ion can be etched during OER to promote the interfacial reconstruction and amorphization, resulting in an improved OER performance with a low overpotential of 196 mV at 10 mA cm −2 and Tafel slope of 29 mV dec −1 ( Chen Z. J. et al, 2021 ). Generally, amorphous structure can offer more active sites and thus exhibit better OER performance compared with their crystalline counterparts.…”
Section: Regulation Of Active Site For Promoting Oermentioning
confidence: 99%